Dietary branched-chain amino acids get to the heart of H3K23Pr - Christina Demetriadou; Daniel S. Kantner; Nathaniel W. Snyder (The Journal of Clinical Investigation, 2023)
Cardiac metabolism provides effects that extend beyond the transformation of energy for the heart to operate effectively. Some metabolites also function as signaling molecules and exert transcriptional changes. Heart failure is a progressive pathology in which these metabolite functions falter. In this issue of the JCI, Yang et al. describe a protective effect from a low–branched chain amino acid (BCAA) diet in a mouse model of heart failure. The findings implicate a propionylation mark on histone H3 lysine 23 (H3K23Pr), previously shown to be dependent on the BCAA isoleucine, in transcriptional control of the cardiac stress response. The result underscores the interplay between metabolism and histone acylation, highlighting targeted dietary and pharmacological intervention as a means to decelerate cardiac hypertrophy.